Writing apprehension among form five students in an ESL classroom / Maslinda Ayu Zainal - Zainal, Maslinda Ayu (2010)
Writing is a demanding activity especially for learners of a second / foreign language and yet it is a skill that they have to master in order to do well in the National Public Examinations which require them to write essays in different formats. Studies have shown that students' writing performance is related to anxiety. This study seeks to find out what are the students' perception and reaction towards writing apprehension. The findings show that the subjects in this study suffered anxiety as a result of their lack of writing skills, and that the better students experienced less anxiety than the weaker ones.